Composite population trends reveal status of wintering diurnal raptors in the Northwestern USA. (January 2023) - McClure, Christopher J.W.; Rolek, Brian W.; Fleischer, Jeff
Abstract: Integrated models can combine data from disparate monitoring programs to improve inference into population dynamics because trends in disparate datasets can be interpreted using a single index. We present a composite index of raptor population trends that combines data from two monitoring programs into a single estimate. The National Audubon Society's Christmas Bird Count and the East Cascade Audubon Society's Winter Raptor Survey use different methods to monitor the same populations of wintering raptors. Observers record all birds detected within 452 km 2 'circles' during the Christmas Bird Count, and during the Winter Raptor Survey observers count raptors along roadways. We present the results of a joint likelihood model that combines trends of raptors counted during both programs into a single population trend from 2005 to 2020. Population indices of the Bald Eagle ( Haliaeetus leucocephalus ), Ferruginous Hawk ( Buteo regalis ), Cooper's Hawk ( Accipiter cooperii ), Red-shouldered Hawk ( Buteo lineatus ), and Red-tailed Hawk ( Buteo jamaicensis ) increased over the course of our study, whereas Prairie Falcon ( Falco mexicanus ) and White-tailed Kite ( Elanus leucurus ) population indices declined. Further, the composite index for White-tailed Kite declined at a rate of 22 % (80 % CRI = 17 %–28 %) per year—supporting evidence of declines from breeding season surveys. We recommend further research into population trends of this species within its core California range. Our study advances efforts to combine trends in datasets collected using differing methodologies to estimate large-scale population trends from disparate data sets. Highlights: Integrated models combine data from disparate monitoring efforts. Our composite index elucidates trends of wintering raptors in the Northwest USA. White-tailed Kite and Prairie Falcon declined from 2005 to 2020. Five raptor species increased from 2005 to 2020.